Evaluating the effectiveness of investment in human capital in the context of digitalization: Ukraine and the European Union - Levytska, Svitlana; Osadcha, Olga; Zinkevych, Oksana; Vovk, Viktoriia (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
The effectiveness of entrepreneurial activity is in the ability to provide not only the positive dynamics of financial and economic performance, but also to address the issue of investing in the formation and development of human capital at the enterprise. The purpose of this article is to study the methodological and organizational approaches to ensuring rational investment in human capital in adaptive terms to processes of digitalization of sustainable development of Ukraine and the European Union. Investments in human capital can be made according to several directions: social (voluntary medical and pension insurance of employees, social benefits for certain categories of employees), health care (payment of medical care, preventive measures and medical examination, financing of physical education and sports) and education (covering expenses for the participation of employees in seminars, conferences, and qualification upgrade courses). Although the final indicators of business and education are completely polar, it is reasonable to consider the assessment of investing in human capital in terms of the effectiveness of these processes. To assess the effectiveness of investment in human capital, a number of methods were considered. Our study of the data provided by the Ukrainian public joint-stock companies in the Management Report for 2019 (information posted on the websites of corresponding companies) confirmed the interest of business entities in supporting the policy of investing in human capital.